APLIKASI RHIZOBAKTERI PEMACU TUMBUH (RPT) DARI AKAR TITONIA (Tithonia diversifolia) TERHADAP PERTUMBUHAN STEK MELATI (Jasminum officinale) PADA ULTISOL - Agustian Agustian; Anisah Permata Sari; Lusi Maira (Jurnal Solum, 2018)
Jasmine plant is a horticultural crop that has promising prospect to be developed in trading. The development of jasmine cultivation is determined by the quality of seedling that can be produced rapidly for planting in the field. The purpose of this research is to study the effect of application of Plant growth-promoting rhizobacteria (PGPR) from titonia root (Tithonia diversifolia) in increasing the growth of jasmine cuttings (Jasminum officinale). This experiment used Completely Randomized Design (RAL) which consists of 7 treatments with 5 replications. The treatments were: A (control), B (Growtone), C (Growtone + 1 ml PGPR), D (Growtone + 2 ml PGPR), E (Growtone + 4 ml PGPR) , F (Growtone + 6 ml PGPR) and G (Growtone + 8 ml PGPR). Data obtained were analyzed statistically with F test at 5% level. The results showed that the application of PGPR can increase the growth of jasmine cuttings. However, the increase in PGPR dose did not have a significant effect on the increase of leaf number, branch number and height of jasmine cuttings. The highest number of leaves, branch and plant height at two months seedling age were found in treatment (C) 1 ml PGPR with 48.60 leaves, 5.80 branch and 22.90 cm plant height that significantly different from other treatments,. Treatment (D) 2 ml PGPR application increased the population of P solubilizing bacteria in rhizosphere from 2.59x104 cfu/g of soil at control to 5.05x105 cfu/g soil and fixing bacteria N (Azospirillium) 3x104 cfu/g soil to 1.41x105 cfu/g soil and Azotobacter to 1.2x 103 cfu/g soil.Key words : Jasmine, PGPR, cuttings, Ultisol